Racializing the Good Muslim: Muslim White Adjacency and Black Muslim Activism in South Africa - Rahman, Rhea (Religions, 2021)
Founded in Birmingham, England in 1984, Islamic Relief is today the world’s largest and most-recognized Western-based Islamically-inspired non-governmental organization. Framed by an analysis of processes of racialization, I argue that Islamic Relief operationalizes not a singular, but multiple Muslim humanitarianisms. I examine what I suggest are competing racial projects of distinct humanitarianisms with regards to HIV and AIDS, health, and wellness. I consider the racial implications of British state-based soft-power interventions that seek to de-radicalize Muslims towards appropriately ‘moderate’ perspectives on gender and sexuality. In South Africa, I argue that Black Muslim staff embrace grassroots efforts aimed towards addressing the material and social conditions of their community, with a focus on economic self-determination and self-sufficiency. I claim that the orientation of these Black Muslim grassroots initiatives denotes a humanitarianism of another kind that challenges the material and ethical implications of a humanitarianism framed within a logic of global white supremacy, and that is conditioned by racial capitalism.